‘Latin American Modernity, and yet...’ - Sharman, Adam (Wiley, 2011)
The article examines two ‘postmodern’ critiques of modernity: a general history which argues that it was never solely Western, and a work of Latin American cultural criticism which wishes to leave a modernity seen as eurocentric. It argues that to understand the modern elements of Latin America entails keeping present the European, and in part pre-nineteenth-century, genealogy of modernity. This, in order to grasp both the pitfalls of claiming modernity is a common project (colonialism vanishes) and the difficulty of going beyond it (European modernity bequeathed the language of breaks and dialectical incorporations). The piece identifies the rhetorical choreography involved when the limits of the critique of Western modernity become apparent.